Bibliometric analysis of rhein in the treatment of tumors - Jiang, Lan; Huang, Qian; Shi, Zhongquan; Yang, Yi (Frontiers in Oncology, 2025)
BackgroundRhein is an anthraquinone compound with a variety of biological activities. It has inhibitory effects on liver cancer, breast cancer, lung cancer, oral cancer, gastric cancer, and other cancers. However, a comprehensive bibliometric review of this field has not yet been published.ObjectiveThis study aims to investigate and evaluate the current research trends and directions about the antitumor properties of rhein using bibliometric analysis.MethodsThe literature related to rhein in cancer treatment from 2003 to 2023 was retrieved from the Web of Science Core Collection (WoSCC) database, and the annual number of publications, main authors, major institutions, keyword clustering, and keyword bursts were visually analyzed using CiteSpace 6.3.R1 software. This study aims to discuss the status quo, hotspots, and development trends of rhein research over the past 20 years.ResultsA total of 220 articles were retrieved from the core collection database, and the number of articles related to treating tumors with rhein increased annually. Among them, Chung, Jing Gung has the highest number of articles in this field, but most researchers lack cooperation with each other. The institutions with the highest number of articles were the Nanjing University of Chinese Medicine (13 articles) and China Medical University (Taiwan) (13 articles). Research hotspots include the promotion of apoptosis, endoplasmic reticulum stress, inhibition of proliferation, drug resistance, and nanoparticles.ConclusionRhein exerts antitumor effects by inducing cell apoptosis, controlling metastasis, and inhibiting proliferation. However, owing to its poor water solubility, in recent years, functional modification of its functional groups or production of rhein nanoparticles to enhance its bioavailability and antitumor effects has become a hot research direction in the future.